2020
DOI: 10.3390/mi11030239
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Insensitive Elastic Surface Electromyographic (sEMG) Electrode for Efficient Recognition of Exercise Intensities

Abstract: Surface electromyography (sEMG) sensors are widely used in the fields of ergonomics, sports science, and medical research. However, current sEMG sensors cannot recognize the various exercise intensities efficiently because of the strain interference, low conductivity, and poor skin-conformability of their electrodes. Here, we present a highly conductive, strain-insensitive, and low electrode–skin impedance elastic sEMG electrode, which consists of a three-layered structure (polydimethylsiloxane/galinstan + pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…According to the number of lines of electrodes, the trend of fill < 3 lines < 1 line was followed. A previous study analyzing the effect of the electrode area on the impedance reported that the impedance decreased with increasing cross-sectional area, indicating an inversely proportional relationship [22,32]. This result was attributed to the area in contact with the skin also increasing due to the increase in the density and area of the conductive material in the electrode of the same size when the amount of conductive yarn was increased.…”
Section: Skin-electrode Impedance Analysis Of the Embroidery Based Te...mentioning
confidence: 89%
See 1 more Smart Citation
“…According to the number of lines of electrodes, the trend of fill < 3 lines < 1 line was followed. A previous study analyzing the effect of the electrode area on the impedance reported that the impedance decreased with increasing cross-sectional area, indicating an inversely proportional relationship [22,32]. This result was attributed to the area in contact with the skin also increasing due to the increase in the density and area of the conductive material in the electrode of the same size when the amount of conductive yarn was increased.…”
Section: Skin-electrode Impedance Analysis Of the Embroidery Based Te...mentioning
confidence: 89%
“…Generally, a higher skin-contact impedance leads to an increased impedance mismatch that reduces common-mode rejection and, hence the SNR (signal to noise ratio) [31,32]. Therefore, it is important to decrease and control the impedance to manufacture an electrode for bio-signals.…”
Section: Skin-electrode Impedance Analysis Of the Embroidery Based Te...mentioning
confidence: 99%
“…Electrical currents generated by muscle contractions can be monitored in the form of EMG signals and displayed on a computer ( Barszap et al, 2016 ). Bioelectricity is detectable when muscle contracts ( Tang et al, 2020 ). Electromyographic techniques are used in sports and rehabilitation accepted by researchers ( Cortez et al, 2017 ; Pakosz and Konieczny, 2020 ; Quittmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that liquid metals have characteristics relating to multiple external stimuli responses, such as temperature, mechanical force, chemical environment, electric field, dielectric field, magnetic field, and even light [ 5 ]. As a result of innovative design principles and processing methods, LM has successfully generated many application prospects, e.g., stretchable sensing systems [ 6 , 7 , 8 ], electrodes [ 9 , 10 ], actuators [ 11 , 12 ], thermoelectric wearables [ 13 ], and energy storage systems [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%